MFRS 102 in frames: an interactive notes for effective revision - Saidi, Noraida; Hassan, Rabaatul Azira; Nik Zam, Nik Zam; Razak, Syuhaila; San, Suzana (Faculty of Accountancy, Universiti Teknologi MARA (UiTM) Cawangan Kelantan, 2025)
Teaching topics like MFRS 102 Inventories, as part of the financial reporting subject, poses a great difficulty for accounting diploma students, as they tend to have problems with understanding concepts and applying them in examinations. This engagement and comprehension challenge motivates the creation of a novel project, which aims to design comic templates that will be used in revision slides specifically related to discussing past exam questions. By combining visual narratives with logical procedures, we hope to develop an engaging and interactive educational experience that aligns with students’ visual cognitive abilities and modern educational approaches. The goal is to create a set of presentation slides that integrate essential theoretical components of the chosen topic with comprehensive solutions to past examination questions. To enhance interactivity, these slides will include a quiz component created through Quizizz.com. These presentation slides will be piloted with students who will be invited to participate in discussion and problem-solving sessions, promoting active learning alongside collaborative learning. The initial results show that enhanced learning materials help with knowledge retention and cognitive overload mitigation while increasing accessibility to complex accounting topics for students. The study argues that comic-based revision slides in accounting education enhances student engagement and performance, supporting cognitive scientists’ research on learners’ retention and visual aids effectiveness. This innovation may also be applied to other financial reporting topics, furthering the goal of making accounting education more interactive and user friendly while preparing learners for real-life situations in the financial industry.